HO CHI MINH’S POLITICAL PERSPECTIVE ON THE VIETNAM-AMERICA RELATIONSHIP FOR THE PURPOSE OF INDEPENDENCE AND FREEDOM IN THE PERIOD OF 1945 – 1946 - Thao, Ngo Thi Phuong (IJRDO- Journal of Educational Research, 2018)
The period 1945-1946 remarked the outstanding abilities and political viewpoint of Ho Chi Minh, especially as a constructor and builder of the relationship between Vietnam and the USA in order to gain freedom and independence. In the foundation of historical knowledge that President Ho Chi Minh bequeathed in such period, the communist Party of Vietnam has been constructing and developing continually the strategic partnership and comprehensive cooperation with the USA in the recent period.